Empowering the Poor through Decentralization : Brazil Rural Poverty Alleviation Program - Kuehnast, Kathleen (World Bank, Washington, DC, 2012)
The Rural Poverty Alleviation Program in Northeast Brazil uses an integrated approach to social and economic analysis in tackling poverty at the community level. Key to the success of this program is the use of economic and social indicators to monitor changes in the community. The reform process encourages the empowerment of the poor and the development of social capital. Those who formerly were socially excluded are now directly involved in institutional development at the local level. Such community-oriented projects encourage new alliances and enable the development of more innovative ways to improve the lives of the rural poor. The components of success in this project are: Community-based empowerment, poverty-targeting mechanisms, decentralization of fiscal and investment decision making from Federal to state and local governments, stakeholder participation, technical assistance and training for beneficiaries, transparency of funding process, an integrated monitoring and evaluation system, and technical assistance and training for beneficiaries, and supervision quality enhanced through a highly effective Management Information System.